Exploring the pharmaco-clinical view on Bhanga (Cannabis sativa linn.): a classical unfamiliar portrayal - Tavhare, Swagata Dilip (International Journal of Pharmaceutical & Biological Archive, 2018)
Bhanga (Cannabis sativa L.),Cannabinaceae family, an annual herbaceous plant, has been used since millennia as a source of medicine, industrial fibre, seed oil, food,recreation, religious and spiritual moods. This fast-growing plant has recently seen a resurgence of interest because of its wide applications. Ayurveda, the science of life, describing many of the formulation about the pharmaco-clinical application of Bhanga but many of these formulations are not in practice today. Indeed; it is a treasure trove of multi-variant Guna (qualities) and Karma (actions), making it a broad spectrum drug. In this review, the rich spectrum of cannabis is being discussed by putting a special emphasis on the formulations containing cannabis either as a major or a minor ingredient. Available 41 Rasagranthas and 26 Chikitsagrantha and other Ayurvedic treatises were referred with respect to Bhanga’s Adhikara (main indication), Kalpana (dosage forms), Anupana (vehicle), Aushadha Sevana Kala (time and period of administration),Pathya- Apathya(do’s and dont’s),Prayojyanaga (parts used), Karma (action), specific uses and instructions of the formulations. It is observed that, there are 210 formulations which contain Bhanga, out of which 193 are recommended for internal administration and 17 for external applications. Among the formulations indicated for internal administration, 102 contain Bhanga as one of the major ingredient, whereas in 91 formulations, it’s a minor ingredient. Nine formulations of external application are having Bhanga as major ingredient and 8 as minor ingredient.The review represents formulations being indicatedof 45 differentRoga- Adhikara, 22 Kalpana,18 Pathya- Apathya, five different parts used, 49 Karma (action) and few benefits and instruction to be followed during administration of formulations containing Bhanga.